Savings natural resource funds: effectiveness of the Norwegian Government Pension Fund Global - Dymitrowska, Yanina (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: Many countries that are rich in natural resources struggle with the resource curse — the phenomenon of achieving worse economic development results by economies specializing in the extraction and export of natural resources. To address this problem, an explicit fiscal tool was proposed — natural resource funds. However, empirical studies on the effectiveness of resource funds conducted so far have delivered mixed and inconclusive results. Specifically, the effectiveness of savings funds, otherwise known as funds for future generations, which are a specific type of natural resource funds, is still being questioned. Aim: This study aims to assess the effectiveness of savings natural resource funds in countries which are rich in natural resources on the example of the Norwegian Government Pension Fund Global (GPFG). Results: The main contribution of this study is to demonstrate the effectiveness of GPFG as a savings fund for future generations. In order to achieve the research objective, a classification of funds was presented and the existing natural resource funds were categorized. Funds were divided into stabilization, investment and savings. The specificity of each type of fund was explained in detail. It was found that all savings funds are also investment funds, but the reverse relationship does not apply. The effectiveness of GPFG was studied considering the functions and tasks of individual fund types. The quantitative study confirmed the effectiveness of GPFG in increasing long-term investments in Norway. At the same time, the fulfillment of the stabilization function by the fund was also validated. The study confirms that the savings fund is an important economic policy measure to counteract the resource curse.